Analysis of Social and Economic Characteristics of Street Vendors in The Kotabaru District of Jambi City (Case Study of Fried Rice Traders) - Mayesti, Indria; Said, Mukti; Halim, Abd; Bambang Niko Pasla (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
This study aims to determine and analyze: 1). Social characteristics of fried rice street vendors; and 2). Economic characteristics of street vendors of fried rice in Kotabaru District, Jambi City. The data analysis method employed is descriptive quantitative analysis. The results of the research are as follows: 1) Social conditions: The average age of the population is 42.78 years, which is the productive age. The highest and most common level of education is SMA/SMK. All Nasi Uduk traders are male. The most common marital status is married. On average, they have been selling for 8.39 years. The average number of family dependents is 5 people. Most have their own houses. The area of origin of most Nasi Uduk traders is Central Java Province. The average length of working hours is 9 hours per day. The average Nasi Uduk trader has his own business and place of business. 2) 2. The majority of business capital is privately owned, with the average initial capital investment being Rp. The average number of days that a business sells its products or services in a given month is 28 days. The average price of a portion of Nasi Uduk is Rp. 16. The average number of servings of Nasi Uduk sold in a given month is 1,338. The average monthly business cost is Rp. The average monthly net income is Rp. 13,973,077. The average monthly consumption is Rp. 7,622,692. The average monthly savings is Rp. 4,474,359. The total amount is Rp. 3,148,333.